An Analytical Study of Construction for Working Wind Turbines in the Areas of Low Speed of the Wind - حسن, أيوب; علي, محمد; عيسى, هيثم; سعيد, مي (Latakia University Journal -Engineering Sciences Series, 2022)
In the shade of increasing crisis of the consumption of the power, and expecting permeation of the fossil fuel, and huge increasing in the prices of the energy especially electrical energy, and dangers of pollution which pervades world. It becomes necessary to use the renewable energy techniques like wind energy especially in the areas which suffer low wind speeds like our coastal area. Therefore, the research tends to create a new mechanism for running the wind turbines by rising the wind speed to the required speed of rotating the wind turbines, and producing electrical energy. the construction consists of heat exchanger which is heating the atmospheric air and its speed is increasing, then the hot air tends towards variable area tower, and at the outlet section of tower there is wind turbine. Therefore, the researcher has studied construction of working wind turbines, and prepared computer program by using Matlab Language, to design variable area tower and chosen the optimal dimensions which achieves low cost and high efficiency.